SOCIAL-PEDAGOGICAL NEED FOR METHODOLOGICAL ASSESSMENT OF THE QUALITY OF EDUCATIONAL ACTIVITIES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Fayziyeva Mabudakhon Mukhammadjonovna (Journals Park Publishing, 2024)
Preschool education plays a crucial role in shaping the future of society by laying the foundation for a child’s lifelong learning. The quality of educational activities in preschool institutions has a significant impact on the cognitive, social and emotional development of the child. This article examines the social and pedagogical need for methodological assessment of the quality of educational activities in preschool institutions. By examining the importance of such assessments, this article aims to demonstrate the importance of ensuring high-quality early childhood education for the comprehensive development of children.
Keywords: Preschool education, educational activities, methodological assessment, quality assurance, pedagogical practice.